Effects of Slag Addition and Mechanical Pre-Processing on the Properties of Recycled Concrete in Terms of Compressive Strength and Workability - Sadagopan Madumita; Malaga Katarina; Lundin Magnus; Nagy Agnes (Nordic Concrete Research, 2021)
Concrete waste as crushed concrete aggregates (CCA) in structural concrete prolongs the technical life of the reference concrete accomplishing closed loop recycling. CCA concrete reaches the reference concrete compressive strength and workability by the densification of CCA and cement paste. Our previous study demonstrates CCA densification by mechanical pre-processing, aggregate quality improvements discerned by increased packing density giving reference concrete strength and workability. This study addresses paste densification with blast furnace slag (GGBS) to replace 30 (wt.%) of Portland cement at reference concrete w/b ratio 0.5 and a lower w/b 0.42. Two CCA replacements are investigated: fine aggregates, CCA50; overall aggregate replacement, CCA100.